2017
DOI: 10.1177/0033294117734834
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grit on the Academic Success of Adult Female Students at Korean Open University

Abstract: This study examined the structural relationship between age, grit (i.e., perseverance of effort and consistency of interest), conscientiousness, self-control, and school success of female students at an Open University in Korea. We analyzed 509 students' responses, and it turned out that the level of perseverance of effort was negatively correlated with academic maladjustment. Also, perseverance of effort had a positive indirect effect on grade point average scores. Conscientiousness and self-control were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 56 publications
(84 reference statements)
5
44
0
2
Order By: Relevance
“…Among 31 studies that examined the effect of consistency of interest on students' academic achievement, 12 reported significant positive results (Hodge et al, 2018;Li et al, 2018;Lin & Chang, 2017;Mason, 2018;Muenks, Yang, & Wigfield, 2018;Rimfeld, Kovas, Dale, & Plomin, 2016;Sheehan, 2014;Williams, 2017), 11 reported nonsignificant results (Akos & Kretchmar, 2017;Dixson, Roberson, & Worrell, 2017;Dixson, Worrell, Olszewski-Kubilius, & Subotnik, 2016;Hwang et al, 2017;W. Lee, 2017;MacCann & Roberts, 2010;Wolters & Hussain, 2015), and three reported mixed results (Kelly et al, 2014;Muenks et al, 2017;Steinmayr, Weidinger, & Wigfield, 2018).…”
Section: Consistency Of Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 31 studies that examined the effect of consistency of interest on students' academic achievement, 12 reported significant positive results (Hodge et al, 2018;Li et al, 2018;Lin & Chang, 2017;Mason, 2018;Muenks, Yang, & Wigfield, 2018;Rimfeld, Kovas, Dale, & Plomin, 2016;Sheehan, 2014;Williams, 2017), 11 reported nonsignificant results (Akos & Kretchmar, 2017;Dixson, Roberson, & Worrell, 2017;Dixson, Worrell, Olszewski-Kubilius, & Subotnik, 2016;Hwang et al, 2017;W. Lee, 2017;MacCann & Roberts, 2010;Wolters & Hussain, 2015), and three reported mixed results (Kelly et al, 2014;Muenks et al, 2017;Steinmayr, Weidinger, & Wigfield, 2018).…”
Section: Consistency Of Interestmentioning
confidence: 99%
“…A total of 31 studies examined the effect of perseverance of effort on students' academic achievement, among which 27 reported a significant positive effect (Akos & Kretchmar, 2017;Dixson et al, 2016;Hodge et al, 2018;Hwang et al, 2017;Li et al, 2018;Lin & Chang, 2017;Mason, 2018;Muenks et al, 2017;Rimfeld et al, 2016;Sheehan, 2014;Steinmayr et al, 2018, studies 1 and 2; Williams, 2017;Wolters & Hussain, 2015), two reported a nonsignificant effect (Dixson et al, 2017;W. Lee, 2017) and one reported mixed results (Kelly et al, 2014).…”
Section: Perseverance Of Effortmentioning
confidence: 99%
See 1 more Smart Citation
“…When the Pearson correlation coefficient was computed for 669 nontraditional doctorate students' grit score and GPA, grit was slightly correlated with GPA for females but not males (Cross, 2014). The high dropout rates in distance learning programs were also of concern to Hwang et al (2017), who attribute academic maladjustment to other obligations such as work or family. To examine the relationship between grit, personality, age, and academic maladjustment, Hwang et al (2017) collected survey results from 509 female students at an Open University in South Korea.…”
Section: Grit and Academic Achievementmentioning
confidence: 99%
“…The high dropout rates in distance learning programs were also of concern to Hwang et al (2017), who attribute academic maladjustment to other obligations such as work or family. To examine the relationship between grit, personality, age, and academic maladjustment, Hwang et al (2017) collected survey results from 509 female students at an Open University in South Korea. They found that age was positively associated with grit, which is consistent with previous studies (Duckworth et al, 2007).…”
Section: Grit and Academic Achievementmentioning
confidence: 99%